Pelatihan dan Pendampingan Usaha Bengkel Mobil Berbasis Added Value dalam Mewujudkan Sustainable Development Goals (SDGS) - Arif Susanto; Fitri Rahmawati; Widiyatmoko Widiyatmoko; Dwicky Ari Ariyanto (Politeknik Kampar, 2025)
The car repair shop business does not only rely on car maintenance services, but is supported by comfortable facilities and excellent service. The car repair shop